Divergence in functional traits in seven species of neotropical palms of different forest strata - Ávalos Rodríguez, Gerardo (2023)
Orlando Vargas facilitated field work at La Selva. Juan Manuel Ley facilitated field work at Tirimbina. Nutrient analyses were facilitated by Floria Bertsch at the Centro de Investigaciones Agronómicas, University of Costa Rica, and by Steven Jansen at the Department of Systematic Botany and Ecology, University of Ulm. The Alpízar Chaves family of El Progreso facilitated work in their property.